2014
DOI: 10.7314/apjcp.2014.15.14.5773
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Human Papillomavirus (HPV) Infection, Cervical Cancer, and HPV Vaccine and its Correlates among Medical Students in Southwest China: a Multi-center Cross-sectional Survey

Abstract: Background: Since cervical cancer can be prevented and controlled through human papillomavirus (HPV) vaccination, it is important to train health care providers and provide them with appropriate knowledge. This study aimed to understand the level of HPV related knowledge among medical students and correlates in Southwest China in order to address any potential gap in their knowledge base. Methods: We conducted a cross-sectional survey among medical students in six selected universities across Southwest China b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 24 publications
4
47
1
5
Order By: Relevance
“…The initiation and progression of cervical cancer is a multi-step process, involving multiple factors and the transformation of normal cervical epithelium into cervical intraepithelial neoplasia, which subsequently transforms into invasive cervical cancer (2,3). A number of studies have demonstrated that persistent infection with high-risk human papillomavirus (HPV) serves an important role in the initiation and progression of cervical cancer (4)(5)(6). However, previous studies have shown that HPV infection alone is insufficient to induce malignant changes and that other factors must contribute to cervical carcinogenesis and progression (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The initiation and progression of cervical cancer is a multi-step process, involving multiple factors and the transformation of normal cervical epithelium into cervical intraepithelial neoplasia, which subsequently transforms into invasive cervical cancer (2,3). A number of studies have demonstrated that persistent infection with high-risk human papillomavirus (HPV) serves an important role in the initiation and progression of cervical cancer (4)(5)(6). However, previous studies have shown that HPV infection alone is insufficient to induce malignant changes and that other factors must contribute to cervical carcinogenesis and progression (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies are underway among Chinese women: Gardasil and Cervarix have already been studied in trials for over four years, while a new HPV 16/18 vaccine by Xiamen Innovax Biotech (Xiamen, China) began the phase III clinical stage in 2013 [22]. An earlier systematic review showed that 69.7% of cervical cancer cases were attributed to HPV 16/18 in China [23], which is similar to the estimate (about 70%) at the global scale [24]. Given these estimates, the efficacy of HPV vaccines in Chinese trials may hopefully not be very much different from those from international studies [13].…”
Section: Introductionmentioning
confidence: 99%
“…No que diz respeito ao desempenho geral dos acadêmicos da PUC-Goiás, a porcentagem geral de acerto foi de 80,0%, superior a todos os outros estudos 19,22,27,28,29 , metodologicamente comparáveis, identificados na literatura especializada. Avaliando o desempenho de acordo com o grupo de conhecimentos, verifica-se um comprometimento maior das questões relacionadas aos sinais e sintomas e diagnóstico do câncer de colo uterino.…”
Section: Resultsunclassified
“…Estudos semelhantes apresentam resultados heterogêneos. Enquanto um estudo32 obteve um nível de conhecimento significativo com 305 acadêmicos na Universidade Kebangsaan da Malásia e Universidade Malaya, nos demais estudos não conseguiram uma conclusão tão esperançosa 19,22,27,28,29 . Na Universidade de Chongqing (China) a média de acerto dentre os 878 estudantes de Medicina participantes foi 45,4%, apesar do conhecimento melhorar com o tempo de estudo na Universidade 19 .…”
Section: Resultsunclassified